Nuremberg and the Crime Against Peace - Roger S. Clark (Washington University Global Studies Law Review, 2007)
Article 5 (1) of the Rome Statute of the International Criminal Court (“ICC”) states that the “crime of aggression” is one of the four “crimes within the jurisdiction of the Court.” Article 5 (2) provides, however, that the Court may not exercise that jurisdiction until a “provision is adopted . . . defining the crime and setting out the conditions under which the Court shall exercise jurisdiction with respect to this crime.” It adds that “[s]uch a provision shall be consistent with the relevant provisions of the Charter of the United Nations.” Having spent a great deal of time in recent years on the negotiations to make Article 5 operational, I thought it might be useful, on this occasion for retrospective thoughts, to review Justice Jackson’s Report on the London Conference at which the Nuremberg Charter was finalized5 and the Nuremberg Judgment itself to examine their approach to the crime against peace. Perhaps if one views them through the prism of the current negotiations something useful might emerge. Not surprisingly, I discovered that many of the issues on the table then are very much on the table now. In particular, in London in 1945 and now, one might characterize the fundamental drafting issue as whether there should be a detailed mens rea and actus reus for the offense or whether it is enough to leave the judges with at most some general references to relevant sources they might take into account. Or indeed, whether it is enough to leave them to figure it out with nothing more than minimal language. This general consideration translates into a number of specific issues, such as the following. One of the basic elements of the crime is an internationally wrongful act by a State—how should that act be described? As a “war of aggression?” and, if so, what is that? Aggression is executed by individuals in the name of the State—how is the connection between the State act and a particular actor to be described? What defenses are open to the defendant—only those personal to him (such as mistake), or may he raise the question of the basic legality or illegality of the State’s allegedly aggressive act itself? For example, claiming that the State was acting in self defense? How far should the drafters anticipate and cut off defenses that an accused might otherwise raise?
Keywords: War crimes; Nuremberg War Crime Trials; Nuremberg; Germany; 1945-1949; Aggression (International law); Conspiracy; Jurisdiction (International law); International